Bioethics dilemmas and their possible solutions in pediatric intensive therapy units of Federal District (Mexico) - Casas Martínez, María de la Luz; Caballero Velarde, María Cristina (Acta Bioethica, 2013)
The process of decision making in pediatric intensive therapy units (PITU) is based on an ethical, legal and scientific framework, which generally is more complex that with adults and involves parents or tutors, thus, it must be solved carefully, with time and methodological precision. A survey was design for experts with anonymous and voluntary application, in a non institutional way, in which questions arise referring to bioethical dilemmas generated in PITU services and proceedings for their solution are proposed. Delphi method was used as instrument in two rounds. The most important results, among others, consisted in recognizing that all physician surveyed face in their unit ethical dilemmas, the most frequent being obstinacy in therapy in 32% cases, result linked to the difficulty to establish the diagnosis of terminal patient in 13% cases. To include bioethics topics and decision making with moral content in training professionals, as well as implementing assertive communication among health care team and families, and promoting adequate functioning of hospital bioethics committees with emergency consulting functions, are proposals which arise from the conclusions of this study.